2021
DOI: 10.1177/0271678x211038138
|View full text |Cite
|
Sign up to set email alerts
|

MRI-visible perivascular spaces in basal ganglia but not centrum semiovale or hippocampus were related to deep medullary veins changes

Abstract: Our purpose is to assess the role of deep medullary veins (DMVs) in pathogenesis of MRI-visible perivascular spaces (PVS) in patients with cerebral small vessel disease (cSVD). Consecutive patients recruited in the CIRCLE study (ClinicalTrials.gov ID: NCT03542734) were included. Susceptibility Weighted Imaging-Phase images were used to evaluate DMVs based on a brain region-based visual score. T2 weighted images were used to evaluate PVS based on the five-point score, and PVS in basal ganglia (BG-PVS), centrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…Using two different radiological PVS markers (high number of smaller-sized PVS and presence of large-sized PVS), we showed that CVR was significantly related to PVS fluid accumulation around damaged small vessels. In agreement with our findings, terminal venous disruptions were associated with decreased interstitial fluid drainage and MRI-visible PVS in the BG [ 33 , 34 ]. The enlargement of the PVS was associated with dysfunctional brain waste clearance involving the glymphatic system and intramural periarterial drainage pathway [ 31 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using two different radiological PVS markers (high number of smaller-sized PVS and presence of large-sized PVS), we showed that CVR was significantly related to PVS fluid accumulation around damaged small vessels. In agreement with our findings, terminal venous disruptions were associated with decreased interstitial fluid drainage and MRI-visible PVS in the BG [ 33 , 34 ]. The enlargement of the PVS was associated with dysfunctional brain waste clearance involving the glymphatic system and intramural periarterial drainage pathway [ 31 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, terminal venous disruptions were associated with decreased interstitial fluid drainage and MRI-visible PVS in the BG. 33,34 The enlargement of the PVS was associated with dysfunctional brain waste clearance involving the glymphatic system and intramural periarterial drainage pathway. 31,35 Thus, our findings highlight the pathophysiological role of cerebral venous circulation in the effects of perivascular fluid drainage on SVD.…”
Section: Discussionmentioning
confidence: 99%
“…The assessments of DMV's visual scores were according to previous studies (Zhang et al, 2017 , 2019 ; Zhou et al, 2020 ; Zhang K. et al, 2021 ). The ESWAN raw data were reconstructed to the magnitude and phase images on a custom-built program on a separate workstation (ADW4.4, GE).…”
Section: Methodsmentioning
confidence: 99%
“…The disruption or decreased visibility of deep medullary veins (DMVs) on susceptibility-weighted imaging has been regarded as the neuroimaging marker of VC in patients with CSVD [ 100 ]. A recent study found that DMVs were associated with EPVS in basal ganglia, suggesting that the disruption of DMVs was involved in glymphatic fluid stasis in the perivascular spaces of basal ganglia [ 101 ]. No association between DMVs and EPVS in centrum semiovale was found; the potential explanation was that cortical and superficial veins and venules drained CSF/ISF in centrum semiovale where the glymphatic function was still functioning normally or in a compensatory phase [ 101 ].…”
Section: The Underlying Role Of the Glymphatic And Meningeal Lymphati...mentioning
confidence: 99%
“…A recent study found that DMVs were associated with EPVS in basal ganglia, suggesting that the disruption of DMVs was involved in glymphatic fluid stasis in the perivascular spaces of basal ganglia [ 101 ]. No association between DMVs and EPVS in centrum semiovale was found; the potential explanation was that cortical and superficial veins and venules drained CSF/ISF in centrum semiovale where the glymphatic function was still functioning normally or in a compensatory phase [ 101 ]. As perivenous space plays a key role in the glymphatic efflux, whether the deposition of collagenosis in venous affects the glymphatic system needs more direct evidence in the future.…”
Section: The Underlying Role Of the Glymphatic And Meningeal Lymphati...mentioning
confidence: 99%